2020
DOI: 10.3390/plants9030339
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of New and Artificial Aged Microplastic and Leachates on the Germination of Lepidium sativum L.

Abstract: With the increase in environmental monitoring and assessing, we are gaining insight into the extent of microplastic pollution in our environment. The threat posed by microplastics to biota could come, e.g., from leached substances. As some plastic materials have been decaying in nature for extended periods already, the toxic effects of leaching compounds need to be investigated. It is furthermore essential to understand the adverse effects of new plastic and how these effects differ from the effects elicited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(46 citation statements)
references
References 39 publications
(50 reference statements)
1
44
1
Order By: Relevance
“…Considering all of the climate parameters that may influence plastic deterioration and leaching, Singaporean plastic litter is more prone to leaching because of the prevailing climate conditions, which is supported by our findings, i.e., that the toxicity of bottle caps collected from Singapore is lower, as the climate-induced faster degradation and leaching of toxic chemical substances. Pflugmacher et al [53] previously demonstrated that the toxicity of polycarbonate to Lepidium sativum decreased with extended ageing time, suggesting that the hazardous chemicals causing the toxicity may leach out as a function of time.…”
Section: Potential Relationship Between Mp Toxicity and Environmental Factorsmentioning
confidence: 99%
“…Considering all of the climate parameters that may influence plastic deterioration and leaching, Singaporean plastic litter is more prone to leaching because of the prevailing climate conditions, which is supported by our findings, i.e., that the toxicity of bottle caps collected from Singapore is lower, as the climate-induced faster degradation and leaching of toxic chemical substances. Pflugmacher et al [53] previously demonstrated that the toxicity of polycarbonate to Lepidium sativum decreased with extended ageing time, suggesting that the hazardous chemicals causing the toxicity may leach out as a function of time.…”
Section: Potential Relationship Between Mp Toxicity and Environmental Factorsmentioning
confidence: 99%
“…On the one hand, those commercial MPs are mainly produced just as chemical reagent, rather than the dominant source from human daily activity. One the other hand, in contrast to their peer in actual environment, the plastic microsphere has too smooth appearance and regular shape without mechanical breakdown, organic corona from biofouling and aging process, due to which the microplastics will exhibit different biochemical behaviors (Fadare et al 2020;P ugmacher et al 2020;Wang et al 2020), including palatability, toxicity and absorption ability. In addition, the environmental MPs contain various kinds of chemical additives, and could cause ecological risk through leaching process (Luo et al 2019), which is rarely possessed by the plastic sphere purchased as pure reagent.…”
Section: Purchased Experiments Materials Lack Representativeness For Environmental Mpsmentioning
confidence: 99%
“…Our bibliographic research found no scientific articles on viridiplantae and MP observations in field studies. Laboratory experiments showed that MPs appear to have limited effects on vascular aquatic plants (Dovidat et al, 2019;Mateos-Cárdenas et al, 2019); for instance, MPs inhibit the growth of shoots and roots (Kalčíková et al, 2017;Pflugmacher et al, 2020). In addition, MPs are adsorbed and accumulated, showing potential depuration activity but at the same time they can be a site of entry into the food web due to the feeding activity of animals (Kalčíková, 2020).…”
Section: Viridiplantaementioning
confidence: 99%